Sizing-design method for compressed air energy storage (CAES) systems: A case study based on power grid in Ontario. (1st February 2023) - Sarmast, Sepideh; Rouindej, Kamyar; Fraser, Roydon A.; Dusseault, Maurice B.
Abstract: Correctly sizing a compressed energy storage (CAES) system by considering external power grid requirements, component limitations, and operation restrictions is essential to successfully enhancing a CAES system's usability and effectiveness. A new method, referred to as the coverage-percentage method, is developed and applied to Ontario as a case study, to size a CAES system based on its percentage ability to capture excess energy and deliver energy during a shortage. The coverage-percentage method builds upon and improves upon the frequency-of-occurrence method proposed by Rouindej et al. (2019) by adding time dependent operation considerations (cavern pressure and temperature), and component limitations (compressor, expander, and cavern sizes). These additional considerations improve both sizing accuracy and usability understanding. One major advantage of the coverage-percentage method is that it rectifies the overestimation of the frequency-of-occurrence method with regards to the percentage of excess energy that can be stored, and stored energy that can be delivered, for a given sized expander, compressor, and cavern. For example, it is observed that a cavern size of 950 MWh for Ontario can capture and deliver 85% of excess energy, while the coverage-percentage method results reveal that a cavern of 950 MWh can actually only cover 48% of Ontario's charging potential. These significantly differing results between the frequency-of-occurrence method and the coverage-percentage method because of the interplay of expander, compressor, and cavern sizes not considered in the frequency-of-occurrence method, but most critically because cavern damaging pressure and temperature limits are not considered in the frequency-of-occurrence method. By applying the coverage-percentage method to 2018 to 2020 Ontario electrical grid data, and to a salt cavern with pressure limits between 5 MPa and 14 MPa, it is revealed that compressors sized between 30 MW to 70 MW, expanders sized between 40 MW to 90 MW, and cavern energy capacities between 630 MWh and 770 MWh would be sufficient to capture at least 42% and 26% of charging and discharging opportunities, respectively. Highlights: Method of coverage-percentage is developed to improve CAES sizing accuracy. The coverage-percentage method includes time dependent operation considerations. The coverage-percentage method introduces usability understanding. A CAES system is proposed for Ontario based on 2018 to 2020 electrical grid data.